Energy consumption in buildings: A correlation for the influence of window to wall ratio and window orientation in Tripoli, Libya. (May 2017) - Alghoul, Samah K.; Rijabo, Hassan G.; Mashena, Mohamed E.
Abstract: This study has been conducted to investigate the influence of window to wall ratio (WWR) and window orientation (WO) on cooling, heating and total energy consumption. The study aims to provide architects with a simple correlation for proper design of facades for office buildings from an energy consumption point of view. The work includes a case study, in which an external wall of a small office space located in the city of Tripoli, Libya was analyzed. Walls with WWR between 0 and 0.9, and with orientation varied in steps of 45° (i.e., facing all eight cardinal and intercardinal directions) were considered. EnergyPlus software was used for energy simulation with "OpenStudio plugin for SketchUp" as an interface. Results indicate that increasing WWR produces an increase in cooling energy consumption and a decrease in heating energy consumption. Cooling energy consumption is found to be substantially higher than heating energy consumption, however, when adding windows to southern walls, cooling consumption drastically increases, while heating energy consumption decreases to zero due to passive solar heating. In general, the effect of adding windows to facade results in an increase in annual total energy consumption by 6–181% for the cases explored in this study. Finally, a correlation representing the relation between total energy consumption, WWR and WO has been established in this paper. Highlights: Windows are responsible for high energy loss from building. Cooling energy consumption is substantially higher than heating in Tripoli. South facing windows increases total energy consumption drastically. Adding windows to facades increase annual energy consumption by 6–181%. A correlation between energy consumption, WWR and WO is proposed.